Shrinking Weibel‐Palade bodies prevents high platelet recruitment in assays using thrombotic thrombocytopenic purpura plasma - Francesca Patella; Chiara Vendramin; Oscar Charles; Marie A. Scully; Daniel F. Cutler (Research and Practice in Thrombosis and Haemostasis, 2021)
Abstract Background Thrombotic thrombocytopenic purpura (TTP), caused by a genetic or autoimmune‐driven lack of ADAMTS‐13 activity, leads to high levels of the ultra‐large von Willebrand factor (VWF) multimers produced by endothelial cells, causing excess platelet recruitment into forming thrombi, often with mortal consequences. Treatments include plasma infusion or replacement to restore ADAMTS‐13 activity, or prevention of platelet recruitment to VWF. Objectives We tested a different approach, exploiting the unique cell biology of the endothelium. Upon activation, the VWF released by exocytosis of Weibel‐Palade bodies (WPBs), transiently anchored to the cell surface, unfurls as strings into flowing plasma, recruiting platelets. Using plasma from patients with TTP increases platelet recruitment to the surface of cultured endothelial cells under flow. WPBs are uniquely plastic, and shortening WPBs dramatically reduces VWF string lengths and the recruitment of platelets. We wished to test whether the TTP plasma‐driven increase in platelet recruitment would be countered by reducing formation of the longest WPBs that release longer strings. Methods Endothelial cells grown in flow chambers were treated with fluvastatin, one of 37 drugs shown to shorten WPBs, then activated under flow in the presence of platelets and plasma of either controls or patients with TTP. Result We found that the dramatic increase in platelet recruitment caused by TTP plasma is entirely countered by treatment with fluvastatin, shortening the WPBs. Conclusions This potential approach of ameliorating the endothelial contribution to thrombotic risk by intervening far upstream of hemostasis might prove a useful adjunct to more conventional and direct therapies.